2008
DOI: 10.1007/s00251-008-0274-6
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Crohn’s disease-associated Nod2 mutations

Abstract: Several lines of evidence have confirmed the importance of Nod2 mutations for disease susceptibility in Crohn's disease. For tracing Nod2 evolution, exons 4a, 4e, 8, and 12 mutations were screened in a collection of 1,064 DNA samples from 52 worldwide populations. The overall allele frequency was 7.5% for single nucleotide polymorphism (SNP)5, 0.2% for SNP8, 0.3% for SNP12, and 0.4% for SNP13. Nod2 mutations are mainly Caucasian alleles with strong distribution dissimilarity between single populations and majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…A number of genes may have coevolved with LP. For example, HLA types, leading to immune signaling,95 and the NOD2/CARD15 system are hypothesized to have evolved in response to drinking milk and the threat of infection 96. Interestingly, genetic mutations in the NOD2 system, which are associated mainly with terminal ileal CD, are largely confined to Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…A number of genes may have coevolved with LP. For example, HLA types, leading to immune signaling,95 and the NOD2/CARD15 system are hypothesized to have evolved in response to drinking milk and the threat of infection 96. Interestingly, genetic mutations in the NOD2 system, which are associated mainly with terminal ileal CD, are largely confined to Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…Gasche et al recently genotyped the three NOD2 mutations in DNA from 7 sub-Saharan African populations (including 25 Yorubans) and did not identify any NOD2 mutations, including Leu1007fsinsC. (46). In a study of 3,575 healthy whites from around the world, NOD2 allele frequency was 7.8% (45).…”
Section: Discussionmentioning
confidence: 99%
“…European-African admixture among AA population has been considered as a continual process over four centuries, and the presence of NOD2 mutations may be affected by survival advantages and disadvantages. For example, NOD2 mutations may produce a survival advantage to exposure to certain infectious pathogens (46, 47). The 1.1% allele frequency we observed among AA controls is lower but within error of that expected from the 20% overall white admixture in AAs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are marked differences in the allelic frequencies of the Nod2 variants among Caucasian populations and geographical regions in Europe (7). Because of these observations, it has been suggested that Nod2 variants linked to CD are under selection pressure possibly through bacterial infections (8). In this report, we show that Nod2 contributes to innate immune responses and regulates survival following infection with Enterococcus faecalis , an enteric commensal that is a common cause of systemic infection and lethality in humans (9).…”
Section: Introductionmentioning
confidence: 99%